The effect of chili pepper-Chinese chives intercropping on rhizosphere microorganisms and root-stem endophytes - Sun, Nan; Wang, Yuxin; Zhang, Ming; Ma, Peifang; Wang, Zhao; Zhao, Haikang; Cao, Caixia (Frontiers in Microbiology, 2025)
IntroductionThis study adopted the intercropping pattern opepper (Capsicum annuum L.) and Chinese chives (Allium tuberosum), combined with high-throughput sequencing and microbial network analysis, to systematically reveal the mechanisms of intercropping on the structural regulation and functional synergy of the crop rhizosphere microbiome and root-stem endophyte communities.MethodsThree treatments were set up: blank control, solo cultivation, and intercropping.Combined with high-throughput sequencing and network analysis, the reorganization patterns of rhizosphere and endophyte communities were systematically analyzed.ResultsIntercropping induced differential responses of microbial communities in the two crops: it significantly increased the bacterial α-diversity in Chinese chives leaves, and the Shannon index of pepper roots also showed an upward trend, while the microbial diversity in pepper rhizosphere soil was inhibited. In contrast, among roots, the “pepper intercropped with Chinese chives” group had the highest total number of OTUs and the largest number of unique OTUs. Microbial communities exhibited cross-host transfer characteristics: the migration rate of microbial communities from pepper roots to Chinese chives rhizosphere reached 46.57%, and 69.54% of the microbial communities in Chinese chives roots originated from pepper roots. Specifically, Aureimonas and Sphingomonadaceae were significantly enriched in pepper leaves, the relative abundance of Pantoea in Chinese chives leaves increased by 11.5 times, and the abundance of Flavobacterium in pepper rhizosphere increased by 94%. Microbial co-occurrence network analysis confirmed the optimization of functional synergy: the proportion of positive interactions in pepper leaves increased to 90.45%, and the negative interactions of Bradyrhizobium decreased by 97%, the proportion of positive interactions of functional bacteria in Chinese chives rhizosphere reached 88.96%, and Bacillus enhanced positive connections while maintaining an abundance of 10.23%–20.87%, the number of positive interactions of Streptomyces in pepper rhizosphere doubled. Network stability showed spatial variation: the robustness of stem microbial networks was significantly improved, while the vulnerability of rhizosphere microbial networks increased.DiscussionThis study provides microbial theoretical support for the intercropping system to optimize nitrogen utilization by driving pepper to enrich the growth-promoting bacteria Sphingomonadaceae, and to enhance disease resistance by promoting Chinese chives to recruit the biocontrol bacteria Bacillus, thereby forming a microecological regulation mechanism with functional complementarity.